Ovarian leiomyoma- An uncommon tumour - Mehreen Yousaf Rana; Hanan, Saima (Journal of the Pakistan Medical Association, 2026)
Primary ovarian leiomyoma is a rare benign tumour of the ovary seen in women between 20 and 65 years of age. We report a case of an ovarian leiomyoma in a 30 years old woman who presented with lower abdominal pain. Ultrasound scan revealed a heterogenous adnexal mass of 12x10cm, raising the possibility of dermoid cyst/teratoma. CA-125 level was 20.81 IU/ml. Laparoscopic removal of an irregular, white, stony hard ovarian mass was performed and histopathological examination confirmed the diagnosis of primary ovarian leiomyoma. Less than 100 cases have been reported in literature so far, including one from Pakistan. The tumour is usually asymptomatic and often misdiagnosed prior to surgical resection, therefore, the diagnosis is frequently made incidentally on histopathology. This rare tumour of the ovary should be considered in the differential diagnoses of solid ovarian masses and surgical intervention with ovary preserving technique is important in young patients. Keywords: Ovary, Leiomyoma, Pathological examination.